KEWENANGAN ABSOLUT PENGADILAN AGAMA TERHADAP PENYELESAIAN KASUS PERBANKAN SYARIâAH (ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 93/PUU-X/2012) - Hasbi, Ghassan Niko; Iswanto, Bambang Tjatur; Mulyadi, Mulyadi (Fakultas Hukum Universitas Muhammadiyah Magelang, 2017)
The provisions on dispute settlement Islamic banking has been laid down in Chapter IX of the settlement of disputes of Article 55 (1), (2), (3) of Law No. 21 of 2008 mentioned that the dispute settlement Islamic Banking is done by the court within the religious court, in case the parties have foretell dispute resolution other than as referred to in paragraph (1), the settlement of disputes in accordance with the contents of the contract, settlement of disputes referred to in paragraph (2 ) must not conflict with Islamic principles. The elucidation of Article 55 paragraph (2) of Law No. 21 of 2008 mentioned that the reference to the settlement of disputes in accordance with the contents of the contract are as follows efforts of deliberation, banking mediation, through the National Sharia Arbitration Board (Basyarnas) or other arbitration institution and / or through the courts within the General Court. The polemic is about the authority to resolve disputes in Islamic banking because there is no dualism of litigation, the Court of religion (Article 55 paragraph (1) of Law No. 21 of 2008) and the District Court stated in the elucidation of Article 55 paragraph (2) of the Act No. 21 of 2008), so in this study took the title of Absolute Authority of Religious Court Case Against Islamic Banking Solution (Analysis Juridical Constitutional Court Decision No. 93 / PUU-X / 2012). This study aims to know the legal implications arising from the decision of the Constitutional Court regarding the absolute authority of the Religious, and the competence of the Religious Islamic Banking in resolving disputes after the publication of the decision of the Constitutional Court for the No. 93 / PUU-X / 2012. The method used in this research is the method of juridical-normative research focus to apply the rules or norms of positive law by finding the law that encourages research, such as looking for the source of various litelatur, interviews with respondents also focused on how the legal aspects and principles of law against the decision of the Constitutional court, and the legal implications of this decision are equipped with primary data (Field research), as well as secondary data which supports research. In this study, there are two principal issues examined is about authority Absolut religious court after the Constitutional Court ruling No. 93 / PUU-X / 2012 as well as the implications of the issuance of the verdict in the world economy, especially sharia Islamic microfinance institutions and Islamic banking. The findings of this research is the decision of the Constitutional Court are legally absolute magnitude against all things Islamic economy both litigation and non-litigation to force the execution of the decision in the case or a decision which is final.